ON THE POSSIBLE NATURE OF Bp-Ap STARS: AN APPLICATION TO HD101065 and HR465 - Gopka, V. F.; Ulyanov, O. M.; Andrievsky, S. M. (Одеські астрономічні публікації, 2007)
We have proposed the new explanation of some magnetic chemically peculiar (MCP) stars anomalies, which is based on assumption that such stars can be the close binary systems with a secondary component being neutron star. Within this hypothesis one can naturally explain the main anomalous features of MCP stars: first of all, an existence of the short-lived radioactive isotopes detected in some stars (like Przybylski's star and HR465), and some others peculiarities (e.g. the behavior of CU Vir in radio range, the phenomenon of the roAp stars).